Dielectric characterization of electro-coagulated boron waste - Okutan, M.; Kavanoz, H. B.; Icelli, O.; Yalcin, Z.; Ay, F.; Delipinar, D.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2014)
The source of electro-coagulation boron waste (ECBW) is wastewater. In order to remove boron from wastewater, boron carried to mud in the form of industrial solid waste is rinsed through electrocoagulation method. The dielectric dispersion properties of the ECBW were analyzed determining the parameters such as complex dielectric functions, dissipation factor and surface conductivity. It is found that at lower frequencies, ECBW sample exhibits a high dissipation factor. The Cole-Cole plots of the sample indicate that the dielectric dispersion mechanism is a Debye type. The boron waste exhibits a high resistance material behavior with a value of 1.03 x 10(9) ohm/sq. and this result is consistent with the electrical behavior of ECBW plate. This study has shown that due to its high resistance and high dielectric dissipation factor, ECBW can be a valuable material for use in many industrial applications which require electrostatic dissipation or electromagnetic shielding. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Alloys; Functional composites; Electrical properties; Powder processing